2023
DOI: 10.3847/1538-4357/acdedd
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Origin of Changing-look Quasar Transitions with Chandra

Qian Yang,
Paul J. Green,
Chelsea L. MacLeod
et al.

Abstract: Extremely variable quasars can also show strong changes in broad-line emission strength and are known as changing-look quasars (CLQs). To study the CLQ transition mechanism, we present a pilot sample of CLQs with X-ray observations in both the bright and faint states. From a sample of quasars with bright-state archival SDSS spectra and (Chandra or XMM-Newton) X-ray data, we identified five new CLQs via optical spectroscopic follow-up and then obtained new target-of-opportunity X-ray observations with Chandra. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 153 publications
0
5
0
Order By: Relevance
“…Over 100 CL AGNs have been discovered based on their Balmer-line profile transitions (MacLeod et al 2016;Gezari et al 2017;Sheng et al 2017;Frederick et al 2019;Green et al 2022;Hon et al 2022;Zeltyn et al 2022;Chen et al 2023;Yang et al 2023), and dozens of CL AGNs have also been identified based on transitions in Mg II, C III], and C IV (Guo et al 2019(Guo et al , 2020Ross et al 2020). However, the nature and frequency of CL AGNs are still not well understood, and many questions remain unanswered.…”
Section: Introductionmentioning
confidence: 99%
“…Over 100 CL AGNs have been discovered based on their Balmer-line profile transitions (MacLeod et al 2016;Gezari et al 2017;Sheng et al 2017;Frederick et al 2019;Green et al 2022;Hon et al 2022;Zeltyn et al 2022;Chen et al 2023;Yang et al 2023), and dozens of CL AGNs have also been identified based on transitions in Mg II, C III], and C IV (Guo et al 2019(Guo et al , 2020Ross et al 2020). However, the nature and frequency of CL AGNs are still not well understood, and many questions remain unanswered.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that CL AGNs preferentially occur at low Eddington ratios (e,g., ∼1%; MacLeod et al 2019;Green et al 2022;Lyu et al 2022;Temple et al 2023), which is an important characteristic of CL AGNs. This Eddington ratio can be analogous to that of the state transition of X-ray binaries (Noda & Done 2018;Ruan et al 2019;Ai et al 2020;Yang et al 2023). When the accretion rate decreases to a few percent of the Eddington limit, an accretion disk can transition from a standard disk to an ADAF, associated with large decrease in far-UV and soft X-ray ionizing photons.…”
Section: Eddington Ratiosmentioning
confidence: 88%
“…The timescale of CL events is approximately 1-10 yr (Ricci & Trakhtenbrot 2023 and references therein), while in the most extreme cases, the broad emission lines can appear/disappear within months (Trakhtenbrot et al 2019;Zeltyn et al 2022). Multiwavelength observations reveal that the appearance of broad emission lines occurs nearly synchronously with variations in the mid-infrared, optical, and X-ray continuum (Sheng et al 2017;Temple et al 2023;Yang et al 2023). Since these behaviors (in addition to the low polarization level observed in turned-off AGNs; Hutsemékers et al 2019) cannot be accounted for by changing obscuration, the driver(s) of the CL phenomenon is generally ascribed to global changes in accretion power (e.g., Elitzur & Ho 2009;Elitzur et al 2014;Ricci et al 2017;Guo et al 2019Guo et al , 2020a.…”
Section: Introductionmentioning
confidence: 99%
“…The absence of observed IR variability in some of our CL-AGNs, however, does not necessarily point to variable obscuration being the source of variability for these sources. To directly determine the source of variability for (each of) the sources identified following the approach presented here (and in similar studies), we would ideally need to conduct a coordinated multiwavelength campaign, including X-ray observations (e.g., LaMassa et al 2015;Ruan et al 2019;Temple et al 2023;Yang et al 2023). This effort is a challenging one due to the extensive data volume of SDSS-V. Alternatively, a careful and detailed spectral analysis may hint at the source of variability (e.g., Ruan et al 2014;Zeltyn et al 2022); such an endeavor, however, is beyond the scope of this work.…”
Section: Accretion Versus Obscurationmentioning
confidence: 99%